Pengaruh Literasi Keuangan, Gaya Hidup, dan Locus of control terhadap Perilaku Keuangan dengan Fintech sebagai Moderasi pada Gen Z Surabaya - Naufal Afif Dwinka Tantra; Nurjanti Takarini (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
The rapid development of financial technology has transformed transactional behavior, particularly among Generation Z. Easy access through mobile banking, particularly BCA Mobile, has made financial activities more practical but also poses risks of consumptive behavior due to low financial literacy and self-control. This study aims to analyze the influence of Financial Literacy, Lifestyle, and Locus of control on Financial Behavior, with Financial technology as a moderating variable. The research population consists of Generation Z users of BCA Mobile in Surabaya. A total of 147 respondents were selected using purposive sampling based on specific criteria. Data were collected through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The findings show that Financial Literacy and Locus of control have a significant positive effect on Financial Behavior, while Lifestyle has a significant negative effect. Furthermore, Financial technology is proven to moderate the influence of Financial Literacy and Locus of control on Financial Behavior, but not the relationship between Lifestyle and Financial Behavior.